New approach of automatic generation control based on absolute rotor angle droop control. Issue 14 (8th June 2018) - Wei, Qiang; Guo, Moufa; Han, Xueshan; Guo, Weimin; Yang, Ming
Abstract : It is being increasingly recognised that the decentralised secondary frequency regulation (SFR) is more suitable for the expanding power systems. Decentralised SFR can more rapidly restore system frequency and damp generator rotor oscillations, as well as relieve the information‐exchange stress between the control centre and widespread generators. Compared to other previously proposed methods, rotor angle droop (RAD) control is simpler and more straightforward. Similar to primary frequency control, the RAD controllers mainly distribute load variance among generators based on their rated capacity. However, they can rapidly and autonomously restore the system frequency without the intervention of a dispatching centre, which makes it more convenient for distributed generation (such as photovoltaic) to participate in frequency regulation. This study shows that the unbalance value between load forecast and real demand can be calculated through absolute rotor angle deviation. This calculated amount can then be reallocated to achieve more economical results. By calculating the area control error and changing the generation in different areas, the tie‐line power flow (PF) can be controlled similarly. However, the fluctuation on the tie‐line PF can be decreased since generators near the loads bear slightly more burden. This is helpful for tie‐line control in large interconnected power systems.